Potential of Soaking and Sun-Drying in Detoxifying Toxic Cassava Root Tubers - Andama, Morgan; Lejju, Julius Bunny; Oloya, Benson (International Journal of Food Science and Biotechnology, 2017)
Root tubers of cassava (Manihot esculenta Crantz) have cyanogenic glucosides which liberate hydrogen cyanide (HCN) on hydrolysis in quantities that can be toxic to humans. As a result, several techniques have been used to detoxify the tubers including among others, soaking, sun-drying and fermentation which has been found to be the most effective. However, fermentation is associated with the growth of potentially mycotoxigenic moulds (fungi) which compromise the quality of the processed product hence suggesting the use of alternative mould free processing techniques like soaking and sun-drying. Therefore, this study investigated the potential of soaking and sun-drying in detoxifying root tubers of a toxic cassava variety, “Rutuga”, (interpreted as “strangler”) of cyanogens (total HCN, free HCN and bound HCN) in South Western Uganda. The cyanogens were determined by a standard titration method. The results indicated that soaking peeled cassava root tubers in cold distilled water for 4 days removed about 78% of bound HCN while sun-drying of peeled cassava chips for 5 days removed about 74% of free HCN. However, both methods are less effective in removing total HCN (soaking, 47%; sun-drying, 43%) due to the ineffectiveness of soaking and sun-drying in removing free HCN (21%) and bound HCN (3%) respectively. cassava of total HCN.
Keywords: Cassava Root Tubers; Cyanogens; Soaking; Sun-Drying